(untitled) (Research, Society and Development, 2024)
The government, in the form of environmental agencies, seeks to control and mitigate the impacts of potentially polluting activities, through the instrument of environmental licensing. The implementation of new real estate developments resulting from urban development often leads to the generation of significant negative environmental impacts on the environment. Within the scope of environmental licensing, the environmental impact study (EIA) and its respective report (RIMA) are mandatory for a list of activities mentioned in the regulatory legislation (CONAMA Resolution No. 1/86). Although this legal provision does not establish the obligation to carry out the environmental impact study of a significant portion of projects, the relevance of the environmental impacts generated by civil construction activities leads to reflection on the extension of the EIA requirement to a greater number of activities under licensing. This research aims to evaluate the relevance of the increase in the requirement of the environmental impact study for a greater number of real estate projects, based on the environmental impacts most verified 6in the implementation phase of these activities. The methodological approach used was the bibliographic survey and the legislative research. As a result, the relevance of carrying out the EIA for a greater number of real estate projects in the context of its environmental licensing was demonstrated, confirming its importance as an instrument to guarantee the fundamental right to a healthy environment.